Congenital Cytomegalovirus Infection Epidemiology, Diagnosis, Therapy (Springer International Publishing, 2018)
This second edition updates the reader on the most common intrauterine transmitted viral infection, CMV. The history of this disease, its pathophysiological background, epidemiology and symptoms, as well as diagnostic and therapeutic strategies, will be discussed in detail. Further a section specifically dedicated to prevention measures is included to the new edition. The chapter on virus-host interaction for defense and transmission is elaborately updated.